2018
DOI: 10.1007/s11250-018-1538-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential of feeding beef cattle with whole corn crop silage and rice straw in Malaysia

Abstract: The potential of using whole corn crop silage and rice straw as an alternative feed for the beef cattle based on the intake and growth performance were evaluated. Using randomised completely block design, nine adult Mafriwal cattle were blocked intro three groups and treated with three different forage diets supplemented with 20% pelleted palm kernel cake on dry matter basis. The treatments were 100% rice straw (RS), 100% corn silage (CS) and an equal mixture of rice straw and corn silage (MIX) fed ad libitum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Recently, Nazli et al [33] studied body weight gain of beef cattle after feeding corn silage, rice straw and combination of both and obtained no significant changes of final live weight which corresponds to this study, although they obtained significant differences for average daily weight gain. Bahri et al [34] also reported significant changes of daily average weight gain of Bali cattle in Indonesia fed different combinations of corn straw and peanut straw silage.…”
Section: Feeding Effect Of Silage On Growth Of Bull Calvessupporting
confidence: 80%
“…Recently, Nazli et al [33] studied body weight gain of beef cattle after feeding corn silage, rice straw and combination of both and obtained no significant changes of final live weight which corresponds to this study, although they obtained significant differences for average daily weight gain. Bahri et al [34] also reported significant changes of daily average weight gain of Bali cattle in Indonesia fed different combinations of corn straw and peanut straw silage.…”
Section: Feeding Effect Of Silage On Growth Of Bull Calvessupporting
confidence: 80%
“…Feed is the major cost of beef production and the current feeding system relies heavily on expensive feed with seasonal usage of fodder grasses while corn silage is very rarely utilised. Currently, no formal production data on corn silage production is available in Malaysia due to very low production [4]. Compared to the conventional feeding system, corn silage is a competitive alternative as it has many advantages for use as ruminant feed.…”
Section: Introductionmentioning
confidence: 99%
“…Bodyweight was measured monthly by the Tru-Test-EC2000 animal weighing balance made in New Zealand (Auckland). Average monthly weight gains (g/d) in different age were calculated by dividing the initial and final body weight differences with the total number of days between two stages of live weights (Nazli et al, 2018). Puberty was defined when a bull produced an ejaculate containing a minimum of 50×10 6 sperm cells with minimum 10% motile (Wolf et al, 1965).…”
Section: Measurement Of Growth Performancementioning
confidence: 99%